2018
DOI: 10.1590/2175-7860201869210
|View full text |Cite
|
Sign up to set email alerts
|

Reproductive traits and floral visitors of Aechmea distichantha plants growing in different habitats of a South American xerophytic forest

Abstract: Aechmea distichantha, a widely-distributed facultative epiphytic bromeliad species, is present from rainforests to xerophytic forests. At its southernmost distribution (Humid Chaco) it grows in the understory and forest edges. This animal-pollinated bromeliad shows high phenotypic plasticity on its vegetative traits, but there is no information about plasticity on its reproductive traits. Infructescences from shade plants were heavier, had longer rachis, more spikelets, higher number of fruits/spikelet and hig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
10
0
3

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(14 citation statements)
references
References 46 publications
1
10
0
3
Order By: Relevance
“…The higher flowering of ramets in the shade is probably associated with milder conditions in the understory. A similar pattern has been recorded for Aechmea distichantha in another study of these forests (Freire et al 2018). In contrast, A. distichantha ramets growing in open areas showed a higher production of ramets than those growing in the understory.…”
Section: Discussionsupporting
confidence: 85%
See 4 more Smart Citations
“…The higher flowering of ramets in the shade is probably associated with milder conditions in the understory. A similar pattern has been recorded for Aechmea distichantha in another study of these forests (Freire et al 2018). In contrast, A. distichantha ramets growing in open areas showed a higher production of ramets than those growing in the understory.…”
Section: Discussionsupporting
confidence: 85%
“…Our previous studies showed that Aechmea distichantha plants exposed to different environmental conditions (i.e. understory vs sunny areas) showed marked differences in leaf anatomy, plant architecture, biomass allocation, and reproductive traits (Cavallero et al 2009(Cavallero et al , 2011Freire et al 2018). Despite these differences between habitats, the present study showed that the dynamic of A. distichantha populations was more affected by the environmental conditions of a particular year than by habitat conditions.…”
Section: Discussionmentioning
confidence: 41%
See 3 more Smart Citations